The Role Of Village-Owned Enterprises In Increasing Green Economic Development In Villages - Mulastih, Listiana Sri; Rohmah , Umdah Aulia; Hardayu, Audisty Prana; Ningsih, Tri Widyastuti; Syofya, Heppi (Universitas Pahlawan Tuanku Tambusai, 2024)
This article comes from the author's service in the villages of Bulak and Bandar Baru for 1 month in these villages. This dedication began with the writer/devotee's sense of concern for villages that have great potential to be invaded by radicalism. This program is also a priority for BNPT and the Government of the Republic of Indonesia.